Diversity. A critical approach - Maloutas, Thomas (The Greek Review of Social Research, 2021)
In this paper ‘‘diversity’’ is scrutinized under four different angles. The first is to place it in a genealogy of scientific and political concepts which describe and assess urban societies, stressing that this concept denotes a further step away from egalitarian discourses and policies. The second is an examination of the relationship between diversity and inequality, inspired by François Dubet’s (2010) elaboration on the relation between unequal class positions and unequal opportunities. The third discusses the relation between diversity and spatial mobility and, particularly, the constrained mobility of labour legitimated based on individuals’ essentialised otherness. The fourth and last angle, is a comment on the relationship between diversity and democracy, pinpointing that the rise of diversity in political discourse has been increasingly concomitant with the limitation of democracy in terms of effective political alternatives as well as in terms of the limited political rights for many of those who constitute this diversity. Overall, the paper stresses the ambivalent relation of policies and discourses promoting diversity with the egalitarian project when the rights of diverse groups are founded on fixed identities and essentialized differences.